PCR for Detection of Herpes Simplex Virus in Cerebrospinal Fluid: Alternative Acceptance Criteria for Diagnostic Workup - López Roa, Paula (American Society for Microbiology, 2013)
The determination of herpes simplex virus (HSV) infection using a PCR assay is one of the most commonly requested tests for analysis of cerebrospinal fluid (CSF), although only a very low proportion of results are positive. A previously reported study showed that selecting only those CSF samples with >5 leukocytes/mm(3) or a protein level of >50 mg/dl was adequate for the diagnostic workup. The aim of the present study was to assess the reliability of alternative acceptance criteria based on elevated CSF white blood cell counts (>10 cells/mm(3)). We analyzed all requests for HSV PCR received between January 2008 and December 2011. CSF samples were accepted for analysis if they had >10 cells/mm(3) or if the sample was from an immunocompromised patient or a child aged <2 years. In order to evaluate our selection criteria, we identified those CSF samples with a leukocyte count of 5 to 10 cells/mm(3) or protein levels of >50 mg/dl in order to test them for HSV type 1 and 2 (HSV-1 and HSV-2) DNA. During the study period, 466 CSF samples were submitted to the microbiology laboratory for HSV PCR. Of these, 268 (57.5%) were rejected, and 198 (42.5%) were tested according to our routine criteria. Of the tested samples, 11 (5.5%) were positive for HSV DNA (7 for HSV-1 and 4 for HSV-2). Of the 268 rejected specimens, 74 met the criteria of >5 cells/mm(3) and/or protein levels of >50 mg/dl. Of these, 70 (94.6%) were available for analysis. None of the samples yielded a positive HSV PCR result. Acceptance criteria based on CSF leukocyte counts, host immune status, and age can help to streamline the application of HSV PCR without reducing sensitivity.